Expanding the Spectrum of EWSR1-NFATC2-rearranged Benign Tumors: A Common Genomic Abnormality in Vascular Malformation/Hemangioma and Simple Bone Cyst. (December 2021) - Ong, Sheena L.M.; Lam, Suk Wai; van den Akker, Brendy E.W.M.; Kroon, Herman M.; Briaire-de Bruijn, Inge H.; Cleven, Arjen H.G.; Savci-Heijink, Dilara C.; Cleton-Jansen, Anne-Marie; Baumhoer, Daniel; Szuhai, Karoly; Bovée, Judith V.M.G.
Abstract : A simple bone cyst (SBC) is a cystic bone lesion predominantly affecting young males. The cyst is lined by a fibrous membrane and filled with serosanguinous fluid. EWSR1/FUS-NFATC2 rearrangements were recently identified in SBC. We here report exactly the same rearrangement in 3 lesions diagnosed as vascular malformations of 2 elderly patients. In total, through Archer FusionPlex, fluorescence in situ hybridization and/or reverse transcriptase-polymerase chain reaction the EWSR1-NFATC2 rearrangement was identified in 6 of 9 SBC, 3 of 12 benign vascular tumors, and none of 5 aneurysmal bone cyst lacking USP6 fusion. Using fluorescence in situ hybridization, it was apparent that amplification of the fusion, as seen in EWSR1-NFATC2 round cell sarcomas, was absent, and that in the vascular tumors the fusion was present both in the lining cells as well as in the surrounding spindle cells. Of note, not all of the spaces in the vascular malformations were lined by endothelial cells. Aggrecan was positive in all cases but was not specific. NKX2-2 and NKX3-1 staining were negative in all cases. Thus, even though the overlap between the 2 entities is limited to the presence of few thick-walled cysts lacking endothelial lining in the benign vascular malformations, the spectrum of benign tumors containing NFATC2 fusions should be expanded and contains not only SBC in the young, but also vascular malformation/hemangioma in elderly patients. Abstract : Supplemental Digital Content is available in the text.